ANALIZA KRYTYCZNA WYBRANYCH REGULACJI PRZEPISÓW KARNYCH KODEKSU SPÓŁEK HANDLOWYCH - Raglewski, Janusz (Zeszyty Prawnicze, 2017)
Critical Analysis of Chosen Penalty Provisions of the Code of Commercial Companies Summary This article is devoted to chosen legislative problems regarding the penalty provisions of the Code of Commercial Companies („CCC”). The considerations of the author are limited to specific issues which in his opinion require prom pt changes. The author’s proposals de lege ferenda regard the following issues: 1) broadening of the subject scope of art. 585 § 1 CCC providing for the penalties for the actions to the company’s detrim ent w ith regard to personal companies; 2) removal of art. 585 § 2 CCC; 3) broadening the liability resulting from art. 586 CCC to all persons which are legally responsible for not filing a m otion for announcem ent of the bankruptcy of a company; 4) changing art. 588 CCC so that it could also provide for the penalties for allowing an acquisition (taking as a pledge) a part of a share by a company; 5) removal of art. 593 as a totally redundant, and 6) defining the legal nature of the regulations included in art. 594 and 595 CCC, accompanied by relevant amendments thereto.